INTEGRASI KESEHATAN MENTAL SEBAGAI PRASYARAT PERNIKAHAN: ANALISIS FIQIH MUNAKAHAT PERSPEKTIF EMPAT MAZHAB - Ainun Nasihah; Nur Faizah (AL-BAYAN INSTITUTE, 2025)
This study aims to analyze the potential integration of mental health assessments as a prerequisite for marriage within the framework of fiqh almunakahat by examining the perspectives of the four major Islamic legal schools: Shafi’i, Hanafi, Maliki, and Hanbali. The background of this research stems from the increasing rates of divorce and family dysfunction linked to the psychological unpreparedness of spouses, while classical Islamic jurisprudence has yet to explicitly address mental health as a formal requirement for marriage validity. This study employs a qualitative library research method using an interdisciplinary approach combining Islamic legal studies, psychology, and civilizational discourse. The findings reveal that all schools acknowledge severe mental illness (junūn) as a type of defect (‘uyub) that can justify annulment (fasakh) of marriage. However, they do not provide a preventive mechanism such as premarital psychological assessment. Within the framework of maqasid alshari‘ah, particularly the preservation of intellect (hifz al‘aql) and life (hifz alnafs), mental health integration as an administrative premarriage policy is both syar’ilegitimate and contextually relevant. This study recommends enhancing religiouspsychological premarital programs and updating fiqh curricula to be more responsive to contemporary psychosocial challenges.